Integrated single-cell RNA-seq analysis reveals the vital cell types and dynamic development signature of atherosclerosis - Shao, Xiuli; Hou, Xiuyang; Zhang, Xiaolin; Zhang, Ruijia; Zhu, Rongli; Qi, He; Zheng, Jianling; Guo, Xiaoling; Feng, Rui (Frontiers in Physiology, 2023)
In the development of atherosclerosis, the remodeling of blood vessels is a key process involving plaque formation and rupture. So far, most reports mainly believe that macrophages, smooth muscle cells, and endothelial cells located at the intima and media of artery play the key role in this process. Few studies had focused on whether fibroblasts located at adventitia are involved in regulating disease process. In this study, we conducted in-depth analysis of single-cell RNA-seq data of the total of 19 samples from healthy and atherosclerotic arteries. This study combines several analysis methods including transcription regulator network, cell-cell communication network, pseudotime trajectory, gene set enrichment analysis, and differential expression analysis. We found that SERPINF1 is highly expressed in fibroblasts and is involved in the regulation of various signaling pathways. Our research reveals a novel mechanism of atherosclerosis, SERPINF1 regulates the formation and rupture of plaques through the Jak-STAT signaling pathway, which may provide new insights into the pathological study of disease. Moreover, we suggest that SRGN and IGKC as potential biomarkers for unstable arterial plaques.